Computational forensics : 5th International Workshop, IWCF 2012, Tsukuba, Japan, November 11, 2012 and 6th International Workshop, IWCF 2014, Stockholm, Sweden, August 24, 2014, Revised selected papers /: 5th International Workshop, IWCF 2012, Tsukuba, Japan, November 11, 2012 and 6th International Workshop, IWCF 2014, Stockholm, Sweden, August 24, 2014, Revised selected papers. (2015) - Unknown
No abstract available